2021
DOI: 10.22219/jamanika.v1i4.19407
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Product Quality and Service Quality on Repurchasing Intention

Abstract: This study aims to examine and analyze the effect of product quality on repurchase intention, service quality on repurchase intention at Café Pesenkopi Malang. The population in this study were all consumers who had bought at a coffee shop using samples is 100 consumers. The sampling technique used snowball sampling and the data collection technique used an online questionnaire through social media. The analysis tool uses Smart PLS 3.0. The results of this study indicate that there is a positive and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
2
4
0
6
Order By: Relevance
“…The findings of this study are consistent with other studies by Rizki et al (2021) and Nugrahaeni et al (2021), which found a positive relationship between the service quality and the repurchase intention. This study demonstrates how providing customers with good, spotless, quick, comprehensive, and accurate service will increase their satisfaction and likelihood of making repeat purchases.…”
Section: Positive Effect Of Service Quality On Repurchase Intentionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study are consistent with other studies by Rizki et al (2021) and Nugrahaeni et al (2021), which found a positive relationship between the service quality and the repurchase intention. This study demonstrates how providing customers with good, spotless, quick, comprehensive, and accurate service will increase their satisfaction and likelihood of making repeat purchases.…”
Section: Positive Effect Of Service Quality On Repurchase Intentionsupporting
confidence: 93%
“…Lovelock & Wright (2012) also stated that if the service quality or quality of service provided by the company approaches or exceeds what consumers expect, then consumers will feel happy, and will really enable consumers to participate to make a repeat purchase. Research by Nugrahaeni et al (2021) and Rizki et al (2021) that demonstrates that service quality variables have a favorable relationship on repurchase intention variables or repurchase interest supports this argument.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 90%
“…Kualitas produk dianggap penting karena mencerminkan kemampuan produk untuk memenuhi atau melebihi harapan konsumen (Made, 2021). salah satu faktornya adalah kualitas produk yang dijadikan sebagai tingkat kemampuan produk untuk memenuhi apa yang diharapkan konsumen dari suatu produk yang dimilikinya (Rizki et al, 2021). Kualitas suatu produk adalah keadaan fisik, fungsi, dan sifat suatu produk yang bersangkutan yang dapat memuaskan selera dan kebutuhan konsumen (Mokoginta et al, 2022).…”
Section: Literature Reviewunclassified
“…Kualitas rasa memiliki pengaruh yang positif signifikan terhadap niat pembelian kembali. (Maulana & Sukresna, 2022), (Made, 2021), (Rizki et al, 2021), (Mokoginta et al, 2022) serta (Pasaribu et al, 2019). Berbanding terbalik dengan hasil (Werdiastuti & Agustiono, 2022).…”
Section: Literature Reviewunclassified
“…This is because consumers have experience in making previous purchases. Therefore, repurchase intention is an important part of consumer behavior (Rizki et al, 2021). Repurchase intention can be identified through 3 dimensions as follows (Kim & Moon, 2009)…”
mentioning
confidence: 99%